Exploring the Origin and Antigenic Specificity of Maternal Regulatory T Cells in Pregnancy - Ahn, Soo Hyun; Nguyen, Sean L.; Petroff, Margaret G. (Frontiers in Immunology, 2020)
Successful pregnancy outcome is partially determined by the suppression of reactive effector T cells by maternal regulatory T cells (TRegs) at the maternal-fetal interface. While a large area of research has focused on the regulation of peripherally-induced TReg (pTReg) distribution and differentiation using transgenic mouse models and human samples, studies focusing on the role of TRegs derived from the thymus (tTRegs), and the potential role of central tolerance in maternal-fetal tolerance is less explored. The genome of the fetus is composed of both the tissue-specific and paternally-inherited antigens, and a break in maternal immune tolerance to either antigen may result in adverse pregnancy outcomes. Notably, “self”-antigens, including antigens that are highly restricted to the fetus and placenta, are promiscuously expressed by medullary thymic epithelial cells under the control of Autoimmune Regulator (Aire), which skews the tTReg T cell receptor (TCR) repertoire to be specific toward these antigens. TRegs that circulate in mothers during pregnancy may be comprised of TRegs that stem from the thymus as well as those induced in the periphery. Moreover, despite a wealth of research dedicated to elucidating the function of TRegs in maternal-fetal tolerance, little is understood about the origin of these cells, and whether/how tTRegs may contribute. Investigation into this question is complicated by the absence of reliable markers to distinguish between the two. In this review, we discuss how distinct types of fetal/placental antigens may determine the generation of different subtypes of TReg cells in the mother, and in turn how these may promote maternal tolerance to the fetus in pregnancy.